An explosion-proof heat insulation film, a heat insulation coating composition, and a method for manufacturing the same

CN122941287APending Publication Date: 2026-10-20SUZHOU LINK FUTURE NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611043643.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0002]现有功能性隔热防爆涂层材料是建筑、交通等领域的重要防护材料,传统产品在配方与工艺上存在诸多技术局限;常规隔热涂料多选用单一类型隔热填料,无法协同兼顾隔热效果与透光性能,实际应用中易出现隔热能力不足或透光性不佳的问题,难以适配高透光需求的使用场景;传统防爆涂层依赖刚性填料提升防护性能,涂层自身韧性较差,受到外力冲击时易发生开裂、脱落,对基材的防爆保护效果有限

Benefits of technology

1、本发明采用多元复合隔热填料与复合防爆增强填料协同搭配,使涂料成膜后同步实现良好的隔热性能与可见光透过性,解决了涂层隔热与透光性能相互制约的技术问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention relates to the field of functional heat-insulating and explosion-proof coating materials, specifically to an explosion-proof heat-insulating film, a heat-insulating coating composition, and its preparation method, comprising the following components: 48 to 68 parts of modified waterborne polyurethane film-forming resin, 25 to 38 parts of composite heat-insulating functional filler, 8 to 16 parts of composite explosion-proof reinforcing filler, 2.2 to 3.8 parts of composite functional additives, and 12 to 18 parts of deionized water. This invention employs a synergistic combination of multi-component composite heat-insulating filler and composite explosion-proof reinforcing filler, enabling the coating film to simultaneously achieve good heat insulation performance and visible light transmittance, thus solving the technical problem of the mutual constraint between the heat insulation and light transmittance performance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional heat-insulating and explosion-proof coating materials, specifically to an explosion-proof heat-insulating film, a heat-insulating coating composition, and a method for preparing the same. Background Technology

[0002] Existing functional thermal insulation and explosion-proof coating materials are important protective materials in fields such as construction and transportation. However, traditional products have many technical limitations in terms of formulation and process. Conventional thermal insulation coatings often use a single type of thermal insulation filler, which cannot simultaneously achieve both thermal insulation effect and light transmission performance. In practical applications, they are prone to problems such as insufficient thermal insulation capacity or poor light transmission, making them unsuitable for application scenarios with high light transmission requirements. Traditional explosion-proof coatings rely on rigid fillers to improve protective performance, but the coating itself has poor toughness and is prone to cracking and peeling when subjected to external impact, resulting in limited explosion-proof protection for the substrate.

[0003] Existing coating formulations lack a systematic combination of functional additives, resulting in weak UV aging resistance. Long-term exposure to outdoor environments can easily lead to yellowing, performance degradation, and poor high and low temperature cycling stability, making coatings prone to defects such as peeling and micro-cracks during use. In the preparation stage, the industry generally adopts conventional one-time mixing processes without special pretreatment and gradient dispersion of functional fillers. This makes fillers prone to agglomeration and makes it difficult to ensure uniform dispersion, directly resulting in significant batch-to-batch differences in coating performance.

[0004] Traditional curing processes often employ a single-temperature constant-temperature curing method, resulting in insufficient resin cross-linking reaction, which prevents the coating from achieving ideal overall performance. Furthermore, the process has low tolerance for errors and is difficult to meet the stability requirements of industrial mass production. Summary of the Invention

[0005] The primary objective of this invention is to provide an explosion-proof heat-insulating film, a heat-insulating coating composition, and a method for preparing the same.

[0006] A further object of the present invention is to provide a heat-insulating coating composition, comprising, by weight, the following components: The mixture comprises 48 to 68 parts of modified waterborne polyurethane film-forming resin, 25 to 38 parts of composite thermal insulation functional filler, 8 to 16 parts of composite explosion-proof reinforcing filler, 2.2 to 3.8 parts of composite functional additives, and 12 to 18 parts of deionized water; the composite thermal insulation functional filler is composed of nano-tin antimony oxide, hollow glass microspheres, and nano-silica; the composite explosion-proof reinforcing filler is composed of polyester flexible short fibers, modified talc powder, and nano-alumina powder; and the composite functional additives are composed of dispersant, defoamer, leveling agent, and UV stabilizer.

[0007] Preferably, the modified waterborne polyurethane film-forming resin is a waterborne high-transparency hydroxyl-modified polyurethane resin.

[0008] Preferably, the mass ratio of nano-tin antimony oxide, hollow glass microspheres, and nano-silica in the composite heat insulation functional filler is 3.5:2:1.2; and the mass ratio of polyester flexible short fiber, modified talc powder, and nano-alumina powder in the composite explosion-proof reinforcing filler is 2.5:3.5:2.

[0009] Preferably, the mass ratio of dispersant, defoamer, leveling agent and UV stabilizer in the composite functional additive is from 1.5:0.6:0.8:0.7 to 2.2:0.9:1.1:1.2.

[0010] A method for preparing the aforementioned heat-insulating coating composition includes the following steps: The composite thermal insulation filler and the composite explosion-proof reinforced filler were respectively subjected to high-speed crushing and dispersion pretreatment to break up agglomerated particles and then filtered through an 800-mesh filter for later use. Surface activation treatment was performed on the polyester flexible short fiber; modified waterborne polyurethane film-forming resin and deionized water were stirred at 750 r / min for 6 min to form a base material, and dispersant, defoamer and leveling agent were added in sequence and stirred for 12 min. The pretreated composite thermal insulation filler was added in three batches at a uniform rate, with an 8-minute interval between each addition. After completion, it was dispersed at high speed. The activated composite explosion-proof reinforcing filler was added and dispersed; a UV stabilizer was added and stirred, and after vacuum degassing, it was cured at room temperature in a sealed environment to obtain a heat-insulating coating composition.

[0011] Preferably, the high-speed pulverization and dispersion pretreatment has a rotation speed of 2900 r / min to 3200 r / min and a treatment time of 20 min to 22 min; the surface activation treatment has a temperature of 50℃ to 52℃ and an activation time of 9 min to 10 min.

[0012] Preferably, the high-speed dispersion speed after the addition of the composite thermal insulation functional filler is 1900 r / min to 2100 r / min, and the dispersion time is 25 min to 28 min; The dispersion speed of the composite explosion-proof reinforced filler was 1650 r / min, and the dispersion time was 30 min; after adding the UV stabilizer, the stirring speed was 600 r / min, and the stirring time was 8 min.

[0013] Preferably, the vacuum degree of the vacuum degassing is -0.085MPa to -0.09MPa, and the degassing time is 18min to 20min; The time for the room temperature sealed curing is 3 hours.

[0014] An explosion-proof heat-insulating film includes a transparent PET base film and a coating applied to the surface of the base film; the coating is formed by curing the heat-insulating coating composition and the dry film thickness of the coating is 35 μm to 40 μm.

[0015] Preferably, the curing process of the coating is as follows: first, pre-curing at 58°C to 60°C for 25 to 28 minutes, and then fully curing at 90°C to 92°C for 42 to 45 minutes.

[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention uses a combination of multi-component composite heat insulation filler and composite explosion-proof reinforcing filler to achieve good heat insulation performance and visible light transmittance simultaneously after the coating film is formed, thus solving the technical problem of mutual restriction between the heat insulation and light transmittance performance of the coating.

[0017] 2. The composite filler system of this invention, combined with flexible reinforcing components, significantly improves the toughness and impact resistance of the coating. The coating is not easily damaged under external force, and it provides outstanding explosion protection for the substrate. At the same time, the coating has excellent adhesion to the substrate, and the interface is tightly and firmly bonded. The matching composite functional additive system effectively improves the coating's resistance to ultraviolet aging. It is not prone to yellowing during long-term outdoor use, maintains stable performance, has excellent resistance to high and low temperature cycling, and is free from appearance and performance defects such as cracking and peeling.

[0018] 3. The present invention adopts a process design of filler graded pretreatment, gradient step dispersion and segmented curing, which completely avoids the problem of filler agglomeration, improves the dispersion uniformity of the system, promotes the full cross-linking of resin, and ensures the balanced and stable performance of coating.

[0019] 4. The process parameters of this invention have a reasonable range of adaptability and good process tolerance. During industrial production, batch consistency is excellent, and high-quality products can be produced stably. The technical solution of this invention takes into account both product performance and production cost. It can meet the stringent protection requirements of high-temperature radiation scenarios and is also suitable for conventional civilian scenarios, thus having good industrialization and promotion value. Detailed Implementation

[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] The modified waterborne polyurethane film-forming resin used in this invention is a waterborne, highly transparent, hydroxyl-modified polyurethane resin with a solid content of 52%, a common film-forming raw material in the coating industry. The dispersants, defoamers, leveling agents, and UV stabilizers used are all conventional additives specifically for waterborne coatings. The nano-tin antimony oxide, hollow glass microspheres, nano-silica, flexible polyester short fibers, modified talc, and nano-alumina used are all commercially available conventional functional fillers for coatings, with particle sizes suitable for coating processing requirements.

[0022] Example 1: This embodiment provides a heat-insulating coating composition, which, by weight, consists of 58 parts of modified waterborne polyurethane film-forming resin, 25 parts of composite heat-insulating functional filler, 16 parts of composite explosion-proof reinforcing filler, 3.2 parts of composite functional additives, and 16 parts of deionized water.

[0023] The composite thermal insulation filler is composed of nano-tin antimony oxide, hollow glass microspheres, and nano-silica in a mass ratio of 3.5:2:1.2.

[0024] The composite explosion-proof reinforcing filler is composed of polyester flexible short fibers, modified talc powder, and nano alumina powder in a mass ratio of 2.5:3.5:2.

[0025] The compound functional additive is composed of dispersant, defoamer, leveling agent and UV stabilizer in a mass ratio of 1.5:0.6:0.8:0.7.

[0026] The preparation process steps in this embodiment are as follows: The composite heat insulation filler and the composite explosion-proof reinforced filler were respectively placed into a high-speed pulverizer and disperser for pretreatment. The pretreatment speed was 3200 r / min and the treatment time was 20 min to break up the agglomerated particles of the filler. After the treatment, they were filtered through an 800-mesh filter for later use.

[0027] Polyester flexible staple fibers were surface activated at 50°C for 10 minutes to improve the bonding performance between the fibers and the resin.

[0028] Add measured amounts of modified waterborne polyurethane film-forming resin and deionized water to a stirred reactor, stir at 750 r / min for 6 min to form a uniform and transparent base material, then add dispersant, defoamer and leveling agent in sequence, and continue stirring for 12 min to achieve uniform fusion of the additives.

[0029] The pretreated composite thermal insulation filler was added to the base material system in three uniform portions, with an 8-minute interval between each addition. After all the materials were added, the mixture was dispersed at a high speed of 2000 r / min for 25 minutes.

[0030] Add the activated composite explosion-proof reinforced filler and disperse at 1650 r / min for 30 min.

[0031] Finally, add the metered UV stabilizer and stir at 600 rpm for 8 minutes. Place the mixture in a vacuum environment of -0.09 MPa for 18 minutes to degas and remove internal air bubbles. Then, allow it to mature at room temperature in a sealed environment for 3 hours to stabilize the system properties and obtain the coating composition.

[0032] A clean and impurity-free transparent PET base film is selected, and the prepared coating is evenly coated on the surface of the base film using a precision coating machine. The dry film thickness is controlled to be 35μm.

[0033] After coating, the film is pre-cured at 60℃ for 25 minutes to complete the shaping, and then fully cured at 90℃ for 45 minutes to promote the full cross-linking of the resin. After naturally cooling to room temperature, the finished explosion-proof and heat-insulating film is obtained.

[0034] Example 2: This embodiment provides a heat-insulating coating composition, which, by weight, consists of 48 parts of modified waterborne polyurethane film-forming resin, 38 parts of composite heat-insulating functional filler, 16 parts of composite explosion-proof reinforcing filler, 3.8 parts of composite functional additives, and 18 parts of deionized water.

[0035] The component mass ratios of the composite thermal insulation filler and the composite explosion-proof reinforced filler are consistent with those in Example 1.

[0036] The compound functional additive is composed of dispersant, defoamer, leveling agent and UV stabilizer in a mass ratio of 1.8:0.7:0.9:0.8.

[0037] The raw material type, filler pretreatment, stirring and dispersion, vacuum degassing, curing and molding process parameters and operation steps used in this embodiment are completely consistent with those in Example 1.

[0038] Example 3: This embodiment provides a heat-insulating coating composition, which, by weight, consists of 68 parts of modified waterborne polyurethane film-forming resin, 25 parts of composite heat-insulating functional filler, 8 parts of composite explosion-proof reinforcing filler, 2.2 parts of composite functional additives, and 12 parts of deionized water.

[0039] The component mass ratios of the composite thermal insulation filler, composite explosion-proof reinforced filler, and composite functional additives are consistent with those in Example 1.

[0040] All preparation process parameters and operating steps in this embodiment are completely consistent with those in Example 1.

[0041] Example 4: This embodiment provides a heat-insulating coating composition, with the basic raw material ratio being completely consistent with that of Example 1.

[0042] The component mass ratios of the composite thermal insulation filler and the composite explosion-proof reinforced filler are the same as those in Example 1.

[0043] The compound functional additive is composed of dispersant, defoamer, leveling agent and UV stabilizer in a mass ratio of 2.2:0.9:1.1:1.2.

[0044] In this embodiment, the parameters for filler pretreatment, fiber activation, base material stirring, vacuum degassing, curing, and solidification are the same as in Example 1. Only the high-speed dispersion process parameters are adjusted: the dispersion speed is adjusted to 2100 r / min, and the dispersion time is adjusted to 28 min. The remaining operation steps remain unchanged.

[0045] Example 5: The raw material formulation and the proportions of each group in this embodiment are completely consistent with those in Example 1. Only some preparation process parameters are adjusted to verify the fault tolerance performance and mass production stability of the process of this invention.

[0046] The specific process parameters are as follows: filler pretreatment rotation speed 2900 r / min, treatment time 22 min; fiber activation temperature 52℃, activation time 9 min; filler high-speed dispersion rotation speed 1900 r / min, dispersion time 30 min.

[0047] Vacuum degassing: vacuum degree -0.085MPa, degassing time 20min. Coating dry film thickness 40μm, low-temperature pre-curing 58℃, pre-curing time 28min, high-temperature curing 92℃, high-temperature curing time 42min.

[0048] The remaining process steps are consistent with those in Example 1.

[0049] Comparative Example 1: The existing high-transmittance heat-insulating coating formula uses the following components by weight: 58 parts modified waterborne polyurethane resin, 25 parts single nano-tin antimony oxide heat-insulating filler, 16 parts conventional talc explosion-proof filler, 3.2 parts conventional additives, and 16 parts deionized water.

[0050] The formula does not contain hollow glass microspheres or nano-silica, nor does it contain polyester flexible short fibers. The entire preparation process is completely consistent with that of Example 1.

[0051] Comparative Example 2: Using the same total proportion, filler compounding ratio, and additive dosage as in Example 1, only the polyester flexible short fibers in the composite explosion-proof reinforcing filler were removed, and only the modified talc powder and nano alumina powder were retained as explosion-proof fillers, while the remaining components and preparation process remained unchanged.

[0052] Comparative Example 3: The conventional formula using existing thermal insulation and explosion-proof fillers in the industry is a simple compounding. By weight, it consists of 60 parts resin, 22 parts thermal insulation filler, 18 parts explosion-proof filler, 2.5 parts additives, and 17 parts deionized water. The filler is compounded in a fixed single ratio.

[0053] The preparation process adopts the industry's conventional room temperature one-time stirring process, without setting up graded pretreatment and gradient step dispersion steps.

[0054] Comparative Example 4: The raw material formula and proportions of Example 1 were used in full, but the graded pretreatment, gradient dispersion and segmented curing processes were cancelled. The conventional one-time feeding and mixing process was adopted, and the low-temperature pre-curing and shaping process was cancelled. The process was directly cured at 90°C for 70 minutes. All other test conditions remained the same.

[0055] The modified waterborne polyurethane film-forming resin used in this invention is a waterborne high-transparency hydroxyl-modified polyurethane resin with a solid content of 52%, which is a conventional film-forming raw material in the field of waterborne coatings; the dispersant, defoamer, leveling agent, and UV stabilizer are all conventional additives for waterborne coatings, and commercially available general models in this field can meet the usage requirements. The nano-tin antimony oxide, hollow glass microspheres, nano-silica, polyester flexible short fibers, modified talc powder, and nano-alumina powder are all conventional functional fillers in the coating field. Their particle size meets the requirements for precision coating processing and does not require special modification treatment.

[0056] In addition, it should be noted that: nano-tin antimony oxide is 30-50nm, nano-silica is 20-40nm, and nano-alumina is 40-60nm; hollow glass microspheres are 20-50μm in size and have a density of 0.25-0.35g / cm³. 3 Polyester staple fiber length 0.8-1.2mm, diameter 10-15μm; modified talc powder 1250 mesh (silane dry modification).

[0057] Fiber activation: Silane KH550 wet activation, the amount of which is 1.2% of the fiber mass, activation at 50-52℃ for 9-10 min.

[0058] Additive types: dispersant is anionic polyacrylate, defoamer is polyether-modified silicone, leveling agent is acrylate, and UV stabilizer is hindered amine.

[0059] Synergistic effect of heat insulation and light transmission: nano-tin antimony oxide reflects and absorbs infrared radiation, hollow glass microspheres construct an insulating air layer, and nano-silica disperses and agglomerates, reducing haze; the combination of the three overcomes the constraints of heat insulation and light transmission.

[0060] Synergistic effect of explosion-proof and toughness: flexible polyester short fibers absorb energy and suppress cracking, modified talc powder filler is added for adhesion, and nano alumina provides rigid reinforcement; the combination of rigidity and flexibility achieves high-efficiency explosion-proof ultra-thin coating.

[0061] Synergistic effect of resin, additives and fillers: High-transparency hydroxyl waterborne polyurethane film formation, special additives ensure dispersion, defoaming, leveling and weather resistance, and the system is compatible and does not stratify.

[0062] Synergistic process and performance: filler pretreatment breaks up agglomerates, gradient dispersion prevents re-agglomeration, segmented curing adapts to PET, vacuum degassing increases density, and batch performance is stable.

[0063] The ambient temperature is 23℃±2℃; the vacuum degree is -0.085MPa--0.09MPa (gauge pressure); the ratio is by weight.

[0064] Test benchmark specification sample benchmark: 50μm transparent PET base film, dry film thickness 35μm; conditioned for 24h at 23℃±2℃ and 50%±5% humidity before testing.

[0065] Visible light transmittance shall comply with GB / T2410-2016.

[0066] Test conditions: Simulated sunlight AM1.5G, 1000W / m 2 UV aging UVA-340, 0.89W / m 2 •nm, 60℃; falling ball impact: 1kg steel ball falls freely from 1m to the center of the sample; high and low temperature cycling: -20℃ to 80℃, 50 cycles.

[0067] Performance testing and results analysis: The dry film thickness of all samples was uniformly controlled at 35 μm, and the test environment temperature was 25℃ with a relative humidity of 55%. Three parallel tests were set up for each group of samples, and the test results were calculated as the arithmetic mean.

[0068] Testing standards: (1) Visible light transmittance shall be in accordance with GB / T2410-2016.

[0069] (2) The infrared thermal insulation temperature difference was tested by simulating continuous sunlight irradiation. After continuous irradiation for 60 minutes, the stable temperature difference value inside the substrate was detected.

[0070] (3) Thermal conductivity shall be in accordance with GB / T10294-2008. Impact and explosion resistance shall be tested by dropping a 1000g standard steel ball from a height of 1m, and the damage state of the coating and the fracture of the substrate shall be observed.

[0071] (4) Coating adhesion shall be performed in accordance with GB / T9286-1998.

[0072] (5) UV weather resistance was tested by 1000h UV aging accelerated test to detect the yellowing degree and overall performance retention rate of the sample.

[0073] (6) The high and low temperature resistance test is carried out by 50 cycles in the temperature range of -20℃ to 80℃, and the surface defects of the coating are observed.

[0074] The test results are shown in Table 1 below: Table 1:

[0075] Results analysis: Based on the above test data, it can be seen that the overall performance of the explosion-proof heat insulation film prepared by the five sets of embodiments of the present invention is better than that of the existing technical solutions of the four comparative examples. The various performances are balanced and stable, and are suitable for actual use conditions. After appropriately increasing the amount of heat insulation filler in Example 2, the infrared heat insulation temperature difference of the coating is significantly improved, the thermal conductivity is effectively reduced, and the heat insulation performance is improved. At the same time, the visible light transmittance remains at a high level, which effectively alleviates the problem of mutual restriction between the heat insulation performance and light transmittance of traditional heat insulation coatings, and is suitable for use in high-temperature radiation scenarios.

[0076] Example 3: After reducing the amount of explosion-proof filler, the coating still maintains good impact and explosion-proof performance and interface adhesion, and the light transmittance is slightly improved. Under the premise of ensuring the core protective performance, the raw material cost is reasonably reduced, which is suitable for conventional civilian protection scenarios and achieves a balance between performance and cost. Example 4: By optimizing the additive ratio and dispersion process, the coating's resistance to ultraviolet aging is effectively improved, the yellowing degree of aging is reduced, the performance retention rate is significantly improved, the weather resistance performance is significantly optimized, and it can be adapted to complex outdoor service environments for a long time.

[0077] After expanding several core process parameters in Example 5, the product's performance remained largely consistent with that of the baseline Example 1, with minimal performance fluctuations. This demonstrates that the technical solution of this invention possesses good process tolerance, can adapt to process fluctuations in conventional industrial production, and exhibits good batch consistency in mass production. All comparative examples exhibited varying degrees of performance defects. The single filler system, lack of a flexible explosion-proof structure, conventional simple compound formulations, and traditional preparation processes all failed to achieve a balanced synergistic effect across multiple performance aspects, resulting in significant shortcomings in product protection performance, weather resistance, and mass production stability.

[0078] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention.

Claims

1. A heat-insulating coating composition, characterized in that, The product comprises, by weight, the following components: 48 to 68 parts of modified waterborne polyurethane film-forming resin, 25 to 38 parts of composite thermal insulation functional filler, 8 to 16 parts of composite explosion-proof reinforcing filler, 2.2 to 3.8 parts of composite functional additives, and 12 to 18 parts of deionized water; the composite thermal insulation functional filler is composed of nano-tin antimony oxide, hollow glass microspheres, and nano-silica; the composite explosion-proof reinforcing filler is composed of polyester flexible short fibers, modified talc powder, and nano-alumina powder; and the composite functional additives are composed of dispersants, defoamers, leveling agents, and UV stabilizers.

2. The heat-insulating coating composition according to claim 1, characterized in that, The modified waterborne polyurethane film-forming resin is a waterborne, highly transparent, hydroxyl-modified polyurethane resin.

3. The heat-insulating coating composition according to claim 1, characterized in that, The composite thermal insulation filler contains nano-tin antimony oxide, hollow glass microspheres, and nano-silica in a mass ratio of 3.5:2:1.2; the composite explosion-proof reinforcing filler contains polyester flexible short fibers, modified talc powder, and nano-alumina powder in a mass ratio of 2.5:3.5:

2.

4. The heat-insulating coating composition according to claim 1, characterized in that, The mass ratio of dispersant, defoamer, leveling agent and UV stabilizer in the composite functional additive is from 1.5:0.6:0.8:0.7 to 2.2:0.9:1.1:1.

2.

5. A method for preparing the heat-insulating coating composition according to any one of claims 1 to 4, characterized in that, Includes the following steps: The composite thermal insulation filler and the composite explosion-proof reinforced filler were respectively subjected to high-speed crushing and dispersion pretreatment to break up agglomerated particles and then filtered through an 800-mesh filter for later use. Surface activation treatment was performed on the polyester flexible short fiber; modified waterborne polyurethane film-forming resin and deionized water were stirred at 750 r / min for 6 min to form a base material, and dispersant, defoamer and leveling agent were added in sequence and stirred for 12 min. The pretreated composite thermal insulation filler was added in three batches at a uniform rate, with an 8-minute interval between each addition. After completion, it was dispersed at high speed. The activated composite explosion-proof reinforcing filler was added and dispersed; a UV stabilizer was added and stirred, and after vacuum degassing, it was cured at room temperature in a sealed environment to obtain a heat-insulating coating composition.

6. The preparation method according to claim 5, characterized in that, The high-speed pulverization and dispersion pretreatment has a rotation speed of 2900 r / min to 3200 r / min and a treatment time of 20 min to 22 min; the surface activation treatment has a temperature of 50℃ to 52℃ and an activation time of 9 min to 10 min.

7. The preparation method according to claim 5, characterized in that, The high-speed dispersion speed after the addition of the composite thermal insulation functional filler is 1900 r / min to 2100 r / min, and the dispersion time is 25 min to 28 min; The dispersion speed of the composite explosion-proof reinforced filler was 1650 r / min, and the dispersion time was 30 min; after adding the UV stabilizer, the stirring speed was 600 r / min, and the stirring time was 8 min.

8. The preparation method according to claim 5, characterized in that, The vacuum degree of the vacuum degassing is -0.085MPa to -0.09MPa, and the degassing time is 18min to 20min; The time for the room temperature sealed curing is 3 hours.

9. An explosion-proof heat insulation film, characterized in that, It includes a transparent PET base film and a coating applied to the surface of the base film; the coating is formed by curing the heat-insulating coating composition according to any one of claims 1 to 4, and the dry film thickness of the coating is 35 μm to 40 μm.

10. The explosion-proof heat insulation film according to claim 9, characterized in that, The curing process of the coating is as follows: first, pre-curing at 58°C to 60°C for 25 to 28 minutes, and then fully curing at 90°C to 92°C for 42 to 45 minutes.